Introducing smart pillow using actuator mechanism, pressure sensors, and deep learning-based ASR - Yang, Seung Hee; Park, Sangwoo; Yang, Taemyung; Jin, Ilhyung; Kim, Wooil; Liu, Chingwei; Kim, Seong-Woo; Eune, Juhyun (ACM International Conference Proceeding Series, 2018)
Sleeping is one of the most essential activities in human lives. It plays a vital role in good health and well-being of human lives. However, WHO (World Health Organization)'s research shows that approximately 27 percent of worldwide population are suffering from sleeping problems, which may affect everyday activities. Amongst various sleeping aid products, pillows can provide the solution to alleviate sleep disorders, neck pain, and chronic fatigue. The adjustable or smart pillows in today's market have some limitations. For instance, there are only few fixed forms and there is only one way interaction from human to the smart pillow. We further improve the existing smart pillow technology in terms of higher transformability and better human-pillow interactions which is bidirectional, thanks to the actuator mechanism, pressure sensors and ASR system.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Actuator mechanism; Augmented Human; Automatic speech recognition; Pressure sensor; Sleeping quality; Smart Pillow